Diagnosis and Treatment of Peritalar Injuries in the Acute Trauma Setting: A Review of the Literature - Abdul R. Arain; Curtis T. Adams; Stefanos F. Haddad; Muhammad Moral; Joseph Young; Khusboo Desai; Andrew J. Rosenbaum (Advances in Orthopedics)
The bony and ligamentous structure of the foot is a complex kinematic interaction, designed to transmit force and motion in an energy-efficient and stable manner. Visible deformity of the foot or atypical patterns of swelling should raise significant concern for foot trauma. In some instances, disruption of either bony structure or supporting ligaments is identified years after injury due to chronic pain in the hindfoot or midfoot. This article will focus on injuries relating to the peritalar complex, the bony articulation between the tibia, talus, calcaneus, and navicular bones, supplemented with multiple ligamentous structures. Attention will be given to the five most common peritalar injuries to illustrate the nature of each and briefly describe methods for achieving the correct diagnosis in the context of acute trauma. This includes subtalar dislocations, chopart joint injuries, talar fractures, navicular fractures, and occult calcaneal fractures.